Survey Pendapat Tenaga Kesehatan Mengenai Aplikasi Pelacakan Kontak Berbasis Android untuk Pencegahan dan Penanganan COVID-19 di DKI Jakarta - Novita Fitria Ningsih; Dedi Nugroho; Benny Efendie; Rizky Farmasita B. (Publikasi Indonesia, 2022)
Coronavirus Disease 2019 (COVID-19) is COVID-19 is an infectious respiratory disease caused by the new virus SARS-CoV-2. SARS-CoV-2 is a new type of coronavirus that has never been detected before in humans. Common signs and symptoms of COVID-19 infection include acute respiratory problems such as fever, cough, runny nose, sore throat and shortness of breath. This study aims to determine the opinion of health workers regarding Android-based contact tracing applications for the prevention and treatment of COVID-19 in DKI Jakarta. This research was conducted on 400 respondents (health workers) who were selected based on inclusion criteria, and this research was in the form of a questionnaire distributed online through the WhatsApp application and Instagram direct message. This research test was conducted descriptively using the SPSS application. The results showed that at the age of 20-40 years as many as 351 (87.8%) respondents knew about Android-based contact tracing applications, while based on gender, 222 (55.5%), female health workers filled out the questionnaires. followed by undergraduate education as many as 166 (41.5%), and the profession of nurses/dentist nurses and midwives as many as 171 (42.8%). Contact tracing applications that have been used in Jakarta consist of Care Protect, Jakarta Now, Ehac Indonesia and alo Dokter. Of these four applications, the most widely used by respondents for contact tracing is care to protect. The contact tracing application needed by respondents is an application that has complete features, is not slow, does not use Bluetooth so that it can save battery power, is easy to use, easy to download, able to track people who may be exposed to COVID-19. So this application is really needed to help reduce the spread of COVID-19 in DKI Jakarta.